Incarvillea semiretschenskia(B. Fedtsch) Grierson as object of Kazakhstan flora biodiversity saving - Winterholler, B.; Winterholler, A.; Auelbekova, A.K. (Fundamental and Experimental Biology, 2015)
The article discusses the issue of the protection of rare populations of Incarvillea semiretschenskiain Chu-Ili mountains, which are left unattended. The authors of this article studied the relic plants, which primarily due to human activities is now threatened with destruction. Incarvillea Juss.— the only genus of herbaceous plants in the family of Bignoniaceae. According to I.D.Illarionova 9 species of inkarvillea grow in Central Asia, one of species — I.Potaninii Maxim. It is endemic of southern Mongolia. Endemic of Kazakhstan Inc. semiretschenskia goes beyond the East Asian type of habitat and is found in the eastern part of the ancient, heavily destroyed Chu-Ili mountains. Saving the rare species of flora in Kazakhstan will help in achieving the main goal — deciphering the phylogeny and development of the concept of the final race. Now especially relevant issues of unique populations are inkarvillei semirechensk in Chu-Ili mountains and generic complex of Incarvillea in Asia.